Pemahaman dan Tantangan Guru Sekolah Dasar Terhadap Penerapan AI dalam Pendidikan - Alfanda, Wahyu; Purwanti, Susi (UNIB Press, 2025)
This research aims to analyze the level of understanding among elementary school teachers in the Southeast Pontianak Cluster regarding the concept of AI technology and its application in learning, identify factors that influence teacher readiness in implementing AI technology in learning, and develop an effective intervention model to enhance teacher capacity in implementing AI technology. The research employs a mixed-method approach with an explanatory sequential design, which combines quantitative methods through a survey of 189 teachers using a Likert scale questionnaireand qualitative methods through in-depth interviews with 24 teachers, 12 school principals, and 6 supervisors, as well as focus group discussions (FGD) involving 36 teachers. Quantitative data analysis is conducted using descriptive statistics, correlation analysis, regression, factor, cluster, and ANOVA using SPSS version 28.0, while qualitative data is analyzed using thematic analysis, content analysis, constant comparative analysis, and discourse analysis with the assistance of NVivo 15. The research results are expected to provide a comprehensive picture of elementary school teacher readiness in adopting AI technology, supporting and hindering factors in its implementation, as well as an intervention model that can help bridge the gap between national policy and field-level implementation. This research is strategic given the role of PGRI Pontianak University as a Training Implementation Institution for coding-based and artificial intelligence learning based on the Decree of the Director General of Early Childhood Education, Basic and Secondary Education for 2025.